LOGISTICAL SERVICE PROVIDER TRIADIC RELATIONAL DYNAMICS - Childerhouse, Paul (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
The concept of supply chain management has evolved from focussing initially on functional co-ordination within an organisation, then to external dyadic integration with suppliers and customers and more recently towards a holistic network perspective. A triad is the simplest meaningful sub-set of a network, and as such will be used as the unit of analysis for this research into relationship continuity and information connectivity of logistical service providers and their associated supply chains. Eight triadic relational states are proposed and the evolutionary paths between them hypothesised based on balance theory. The fundamental roll of logistical service providers is examined within these alternative triadic states with a specific focus on the relationships between the actors. Empirical evidence is collected from two very different triads. Historical information is gathered on the evolution of these two cases and cross-referenced with our proposed evolutionary triadic model. How the interactions and relationships change over time is the central focus of the case investigation and the conceptual model. Our initial findings indicate that some networks are more stable than others and depending on their position in a triad some actors can gain power over their business partners. Further, those organisations that act as information conduits seem to have greater capacity to influence their standing in a supply chain network.